(untitled) (Advancements in Homeopathic Research, 2022)
Disease is a process which may begin initially with insidious common symptoms as malaise, weakness, pain, etc.; in the body and gradually physiological sign(s) occur and finally ends in pathological sign(s) and symptoms. Or a disorder of function or structure in human body, one that produces specific symptoms and sign(s). It can be acute in nature e.g. pneumonia or/ and chronic in nature e.g. rheumatic or osteoarthritis. Cancer takes a long process being genetic or otherwise, may be from childhood (e.g. retinoblastoma) to adult age. In Homoeopathy all chronic diseases/conditions are due to three Chronic Miasms which are Psora, Sycosis and Syphilis (1, Para. 78, 79, 80, 81 and its footnotes, 206) by Hahnemann. These were/are facts and not delusions.